ChemInform Abstract: Transnitrilation from Dimethylmalononitrile to Aryl Grignard and Lithium Reagents: A Practical Method for Aryl Nitrile Synthesis. Issue 3 (29th December 2015) - Reeves, Jonathan T.; Malapit, Christian A.; Buono, Frederic G.; Sidhu, Kanwar P.; Marsini, Maurice A.; Sader, C. Avery; Fandrick, Keith R.; Busacca, Carl A.; Senanayake, Chris H.
Abstract: The reaction of commercially available or in situ generated Grignard reagents with dimethylmalononitrile (II) affords desired aryl nitriles (III), (V), and (VII) in good to high yields.